Impact of Air-Purifying Plants on the Reduction of Volatile Organic Compounds in the Indoor Hot Desert Climate - Al Qassimi, Nahla; Jung, Chuloh (Frontiers in Built Environment, 2022)
Due to hot desert weather, residents of Dubai spend 90 % of their time indoors and the interior environment of the newly built apartments with inappropriate material and ventilation is causing sick building syndrome (SBS), faster than in any other country. NASA studies on indoor air pol-lutants indicate that the usage of 15–18 air purifying plants in 18–24 cm diameter containers can clean the air in an average 167.2 m2 house ( approximately one plant per 9.2 m2). This study in-vestigates the effect of three different types of air purifying plants, Pachira aquatica, Ficus ben-jamina, and Aglaonema commutatum, in reducing volatile organic compounds (VOCs) and formaldehyde (CH2O). An experiment is performed in which the formaldehyde (CH2O) and VOC concentrations are measured in two laboratory spaces (Room 1 and Room 2). Different volumes (5 % and 10 % of the laboratory volume) of target plants are installed in Room 1, whereas Room 2 is measured under the same conditions without plants for comparison. The results show that the greater the planting volume (10 %), the greater is the reduction effect of each VOC. In summer, the initial concentration (800 µg/cm3) of formaldehyde (CH2O) and VOCs is higher, and the reduction amount is higher (534.5 µg/cm3) as well. The reduction amount of formaldehyde (CH2O) and toluene (C7H8) are particularly high. In the case of toluene (C7H8), the reduction amount (45.9 µg/cm3) is higher in summer with Aglaonema commutatum and Ficus benjamina. It is statistically proven that Ficus benjamina is most effective in reducing formaldehyde (CH2O) and toluene (C7H8) in an indoor space. The findings of this study can serve as basic data for further improving the indoor air quality using only air purifying plants in hot desert climates such as in Dubai, United Arab Emirates.